Change Management Analysis of SAP - Shylko, Aliaksei (2014)
This thesis is dedicated to the topic of Change Management and how this process is organized in SAP, world leader in enterprise applications in terms of software and software-related service revenue. The thesis has 3 main objectives: to create a theoretical overview of change and change management-related aspects based on literature review, to analyze how the change management process is designed in SAP, on which methodology it relies and which tools are supporting the smooth process flow. The thesis contains as well numerous examples of real transformation projects and tools, which were driven by SAP in the last couple years. 3rd objective is concerned with the analysis of change perception in different geographical locations, where SAP has its SSCs (Shared Services Centers). This covers such places as Dublin, Singapore, Buenos Aires and Prague. In order to enhance the change awareness among SAP employees and decrease the level of resistance to change, a special Survey was designed to assess the current level of knowledge in change-related topics and preferences. Based on the results, the recommendations were created in order to further support the change initiatives.